Synthesis and characterization of π-conjugated copolymers with thieno-imidazole units in the main chain: application for bulk heterojunction polymer solar cells. Issue 12 (27th February 2015) - Keshtov, M. L.; Godovsky, D. Yu.; Chen, F. C.; Khokhlov, A. R.; Siddiqui, S. A.; Sharma, G. D.
Abstract : Three D–A conjugated copolymersP1, P2 andP3 based on different weak donors and the same acceptor unit, were used as donors for BHJ solar cells and achieved a PCE of 6.76%. Abstract : In this paper the three new narrow bandgap D–A conjugated copolymersP1, P2 andP3 based on different weak donor fused thiophene-imidazole containing derivatives and the same benzothiadiazole acceptor unit were synthesized by Stille cross-coupling polymerization and characterized by 1 H NMR, elemental analysis, GPC, TGA, DSC. These copolymers exhibit intensive absorbance in the range 350–900 nm and the optical bandgap lies in the range of 1.50–1.61 eV, which corresponds to the maximum photon flux of the solar spectrum. The electrochemical bandgap derived from cyclic voltammetry varies within the limits 1.47–1.65 eV and is approximately very close to the optical bandgap. The highest occupied molecular orbital (HOMO) energy level of all copolymers is deep lying (−5.24 eV and −5.37 eV and −5.25 eV forP1, P2 andP2, respectively) which shows that copolymers have good stability in the air and assured a higher open circuit voltage ( V oc ) for polymer BHJ solar cells. These copolymers were used as donors along with PC71 BM and the BHJ polymer solar cells based onP1 :PC71 BM, P2 :PC71 BM andP3 :PC71 BM processed from chloroform (CF) solvent with 3 v% DIO as an additive showed an overall PCE of 4.55%, 6.76% and 5.16%, respectively.